(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Military terminology refers to the terms and language of military organizations and personnel as belonging to a discrete category. As distinguishable by their usage in military doctrine, they serve to depoliticise, dehumanise, or otherwise abstract discussion about its operations from an actual description thereof